Non-Carbon-Based Fuels (specialty section of Frontiers in Fuels) - (:unkn) unknown (My University, 2026)
As an Editor, you will finalize the Topic's scientific vision and scope, identify and invite potential authors, and handle the peer review for a portion of the submitted manuscripts.